Apa Dampak Employee Engagement Terhadap Kinerja Pegawai pada Koperasi Simpan Pinjam Mitra Sarana Karya Bandung - Ajeng Nurdini; Yayan Firmansyah (Jurnal Multidisiplin Madani, 2022)
Several previous studies have shown a relationship between employee engagement which has a positive effect on performance. This study aims to conduct a study related to the effect of employee engagement on employee performance at Kosipa MSK. The census sampling method was 33 employees. The data obtained is then processed using a causal model with the help of SmartPLS software. The results obtained that support the general theory of employee engagement where employee engagement affects employee performance by 43%, so there are still 57% of factors that affect the performance of other variables. This study provides suggestions for further researchers to expand the object of research and its longitudinal study in addition to that employee engagement can be a moderator variable to determine employee performance.